Ranking islamic corporate social responsibility activities under product development theme using analytic hierarchy process / Shahida Farhan Zakaria ... [et al.] - Farhan Zakaria, Shahida; Wan-Abu-Bakar, Wan-Asma‘; Said, Roshima; Syed-Noh, Sharifah Nazura; Ahmad, Abd-Razak (2015)
Corporate social responsibility (CSR) initiatives are becoming more popular as companies realize the positive impact the CSR activities have on the goodwill of the companies. For shariah compliant companies the CSR activities or policies must cater to the concept of maslahah (public good or interest) and satisfy the objectives of Shariah. In this paper we aim to help companies identify important CSR activities which are of more interest to the consumers. Using analytics hierarchy process, we rank the importance CSR activities and policies implemented by companies when developing their products. The results of the analysis showed that activities and policies that are deemed as important are ‘developing products that have safety features’, ‘disclosing products that meet safety standards’, and ‘training employees in developing safety standards for processes’.